Phenolic-Protein Interactions: Effects on Food Properties and Health Benefits - Buitimea-Cantúa, Nydia E; Gutiérrez-Uribe, Janet A; Serna-Saldívar, Sergio O (Journal of medicinal food, 2018)
Phenolic-protein interactions (PPI), which naturally occur in most food systems, are being intentionally designed to enhance functional performance of phenolic compounds (PC). PPI have been primarily associated with changes related to sensorial, nutritional, and nutraceutical features of foods. Furthermore, these interactions affect properties such as astringency, protein digestibility, absorption, and bioavailability of antioxidants. Therefore, new product development should pay attention to these interactions and not only on the concentration of PC. PPI protect PC from degradation due to enzymatic attack or pH changes in the lumen of the intestinal tract. Due to PPI, PC are delivered to the colon where they are metabolized by the microbiota and generate an antioxidant environment. Interactions with proteins also may enhance the antiproliferative activity of PC in some specific tumor cell lines. In this review, the effects of PPI that affect both food properties and health benefits are discussed.